Examples and Non Examples Learning Training to Determine The Reading Ability Of Primary School Students - Saipul Wakit; Margiyono Suyitno; Ainur Rha’in (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Education is a conscious effort to improve knowledge, skills and shape students' character. Education does not only prioritize cognitive skills but also combines several elements to become a person who believes and is devoted to God Almighty. In the context of basic education, the foundation that must be instilled is student character supported by cognitive knowledge such as writing, reading and basic knowledge. Seeing the reality, not all elementary school students can read or spell as expected, as is the phenomenon found in elementary schools in the Jember district. To overcome this, a training activity was carried out using exaples and nonexaples methods to increase students' knowledge and skills in reading. This activity method is carried out through training and simulations for students starting with the planning stage, implementing activities, and evaluating post-training activities. The results of this activity showed that there were around 26 elementary school students who could not read and spell well and correctly. Apart from that, teachers' knowledge and skills have increased in guiding students to be able to read and spell using exaples and nonexaples methods.